2001
DOI: 10.1109/58.971706
|View full text |Cite
|
Sign up to set email alerts
|

A model for phase noise generation in amplifiers

Abstract: In this paper, a model is presented for predicting the phase modulation (PM) and amplitude modulation (AM) noise in bipolar junction transistor (BJT) amplifiers. The model correctly predicts the dependence of phase noise on the signal frequency (at a particular carrier offset frequency), explains the noise shaping of the phase noise about the signal frequency, and shows the functional dependence on the transistor parameters and the circuit parameters. Experimental studies on common emitter (CE) amplifiers have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(1 citation statement)
references
References 11 publications
(16 reference statements)
0
1
0
Order By: Relevance
“…3 shows what happens if the reactance's flicker noise is assumed to be negligible, α X = 0. With zero flicker coefficient of losses (a), the amplitude PSD is only 7 There had been a discussion in the literature about the actual phase PSD's slope of the crystal resonator beyond the half bandwidth (see a brief review in [8]). Some authors had brought forward evidence for near f −2 , and others had shown the measurement with almost f −3 .…”
Section: L(f) = 10 Log[s(f)] (51)mentioning
confidence: 99%
“…3 shows what happens if the reactance's flicker noise is assumed to be negligible, α X = 0. With zero flicker coefficient of losses (a), the amplitude PSD is only 7 There had been a discussion in the literature about the actual phase PSD's slope of the crystal resonator beyond the half bandwidth (see a brief review in [8]). Some authors had brought forward evidence for near f −2 , and others had shown the measurement with almost f −3 .…”
Section: L(f) = 10 Log[s(f)] (51)mentioning
confidence: 99%